Pengaruh Rasio Solvabilitas, Likuiditas Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Pada Perusahaan Konstruksi Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2020-2024 - Putri Melani; Dwi Saraswati; Hendra Saputra (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2025)
The aim of this research is to examine how solvency ratios, liquidity, and company size influence the financial performance of BEI construction from 2020 to 2024. Return on Assets (ROA) is used as the dependent variable to measure financial performance, while Debt to Asset Ratio (DAR), Cash Ratio (CR), and the natural logarithm of total assets (Ln Total Assets) are used to measure solvency, liquidity, and company size. This research uses a quantitative methodology that uses a multiple linear regression analysis approach. Purposive sampling was used to choose the sample, which included 80 observations from a total of 16 companies over a 5-year period. Based on the research findings, it can be concluded that while firm size has a substantial impact on financial performance, the solvency and liquidity variables have no significant impact on financial performance. At the same time, financial performance is significantly impacted by solvency, liquidity, and company size. It is hoped that these findings will contribute to the body of knowledge in the field of corporate finance and provide investors and company management something to think about when making financial decisions.